Teenager's Perception of Kpop Cultural Adaptation In Indonesia - Sudwintari, Sudwintari; Perangin-angin, Alemina Br (Talenta Publisher, 2022)
Abstract. This research discusses about teenager's perception of kpop cultural adaptation in indonesia. The method is KPOP cultural adaptation for used in this research qualitative by is descriptive using a narrative approach with the main target is the teenagers in Indonesia. The results of writing this discussions obtain the information about the close relationship between cultural and adaptation of Korean in Indonesia. KPOP cultural adaptation consists of teenager's perception about things that will discuss are how many teenagers in Indonesia like kpop, the extent to which they know about kpop, the reasons that underlie this teenagers like kpop. Things they do to support their idol KPOP and also their opinions about the impacts that are caused by the existence of KPOP in Indonesia. Keyword: Cultural Adaptation, Indonesia, KPOP, Teenager’s perception Abstrak. Penelitian ini membahas tentang persepsi remaja terhadap adaptasi budaya KPOP di Indonesia. Metode yang digunakan dalam adaptasi budaya KPOP adalah penelitian kualitatif dengan metode deskriptif menggunakan pendekatan naratif dengan sasaran utama adalah remaja di Indonesia. Hasil dari penulisan diskusi ini memperoleh informasi tentang hubungan erat antara budaya dan adaptasi bahasa Korea di Indonesia. Adaptasi budaya KPOP terdiri dari persepsi remaja tentang hal-hal yang akan dibahas adalah berapa banyak remaja di Indonesia menyukai KPOP, sejauh mana mereka tahu tentang KPOP, alasan yang mendasari remaja ini menyukai KPOP. Hal-hal yang mereka lakukan untuk mendukung KPOP idola mereka dan juga pendapat mereka tentang dampak yang ditimbulkan oleh keberadaan KPOP di Indonesia. Kata Kunci : Adaptasi Budaya, Indonesia, KPOP, Persepsi Remaja